High-strength enameled copper flat wire and preparation method thereof

By adding modified carbon fiber powder to the polyimide enameled wire paint and performing specific modification treatment, the problem of insufficient mechanical properties of polyimide enameled wire in extreme environments is solved, and the improvement of high strength and thermal stability is achieved.

CN119446670AInactive Publication Date: 2025-02-14ZHEJIANG SANHANG ELECTRIC TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411524443.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polyimide enameled wires show insufficient mechanical properties in extreme environments, especially when temperature changes, paint film cracking may occur, affecting its mechanical properties.

Method used

By adding modified carbon fiber powder to polyimide enameled wire paint, and subjecting acid oxidation treatment and grafting polyamide-amine treatment, the binding force between carbon fiber powder and polyimide resin paint is enhanced, and the paint film is enhanced Thermal stability and mechanical properties.

Benefits of technology

The mechanical strength and thermal stability of the enameled copper flat wire are significantly improved, and the paint film cracking caused by temperature changes is avoided, ensuring performance and reliability in harsh and extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a high-strength enameled copper flat wire and a preparation method thereof, and belongs to the technical field of enameled wires. Comprising the following steps: adding polyimide resin into a solvent, dissolving to obtain a polyimide solution, adding modified carbon fiber powder into the polyimide solution, and uniformly stirring to obtain the wire enamel, and uniformly coating the surface of the copper flat wire with wire enamel, and then carrying out heating curing treatment to obtain the high-strength enameled copper flat wire. The enameled wire has high mechanical strength and can be used in harsh extreme environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of enameled wires, and in particular to a high-strength enameled copper flat wire and a preparation method thereof. Background Art

[0002] As a special electromagnetic wire, enameled copper flat wire plays an important role in the modern electrical industry due to its unique properties and wide application. The history of enameled copper flat wire can be traced back to the end of the 19th century. With the rise of the electric power industry, the demand for high-performance wires has been growing. The original enameled wire was round, but with the advancement of technology and the diversification of application scenarios, flat wires have gradually developed due to their advantages in specific applications. In the mid-20th century, with the development of plastics and chemical technology, the insulation materials and manufacturing processes of enameled copper flat wires have been significantly improved. Insulating varnish is an important component of enameled copper flat wire, which provides electrical insulation and physical protection. Insulating varnish is usually composed of resin, solvent and additives. Resin is the basis of varnish and determines the insulation performance and thermal stability of varnish. Solvents are used to adjust the viscosity and fluidity of varnish, while additives are used to improve specific properties of varnish, such as chemical resistance, wear resistance, etc.

[0003] Polyimide wire enamel is a high-performance insulating coating, mainly used for the insulation layer of wires and cables. Polyimide wire enamel is an insulating coating with polyimide resin as the main component. It is coated on copper wire or other metal wires through a specific process and forms an insulating layer after heating and curing. In high-end application fields such as aerospace, military equipment, and high-speed railways, wires and cables may be exposed to extreme environmental conditions. Improving the mechanical strength of wire enamel can ensure performance and reliability under these harsh conditions.

[0004] Therefore, it is necessary to develop a new type of polyimide enameled wire to further improve the mechanical strength of the polyimide enameled wire. Summary of the invention

[0005] The purpose of the present invention is to solve the above technical problems and propose a high-strength enameled copper flat wire and a preparation method thereof. The enameled wire of the present invention has high mechanical strength and can be used in harsh and extreme environments.

[0006] The technical solution of the present invention is achieved in this way:

[0007] A method for preparing a high-strength enameled copper flat wire comprises the following steps:

[0008] 1) adding a polyimide resin into a solvent to dissolve the polyimide resin to obtain a polyimide solution, adding the modified carbon fiber powder into the polyimide solution, and stirring the mixture to obtain a wire enamel;

[0009] 2) The enameled wire varnish is evenly coated on the surface of the copper flat wire, and then heated and cured to obtain a high-strength enameled copper flat wire.

[0010] Preferably, in step 2), the thickness of the wire enamel coated on the surface of the copper flat wire is controlled to be 30-50 um.

[0011] Preferably, in step 2), the heating curing temperature is 150-180° C., and the heating curing time is 3-7 hours.

[0012] Preferably, the method for preparing the modified carbon fiber powder in step 1) comprises the following steps:

[0013] 11) placing the carbon fiber powder in a mixed solution of nitric acid and acetone for acid oxidation treatment, filtering, separating, washing and drying to obtain oxidized carbon fiber powder;

[0014] 12) adding γ-glycidyloxypropyltrimethoxysilane to a mixed solution of ethanol and water, stirring and hydrolyzing to obtain a hydrolyzate, adding the oxidized carbon fiber powder to the hydrolyzate, heating for reaction, filtering, separating, washing and drying to obtain a pre-modified carbon fiber powder;

[0015] 13) Add the pre-modified carbon fiber powder into the polyamide-amine aqueous solution, heat to 80° C., stir to react, filter, separate, wash and dry to obtain the modified carbon fiber powder.

[0016] In the technical solution of the present invention, the mechanical strength of polyimide wire enamel is improved by adding carbon fiber powder to it. Carbon fiber has the characteristics of high modulus and high strength, can evenly distribute stress, reduce stress concentration, and when carbon fiber is evenly dispersed in the polyimide matrix, it can effectively bear the load, thereby improving the mechanical properties of the material. However, the team of the present invention found that after adding carbon fiber powder to polyimide resin wire enamel, after subsequent heating and curing treatment, a small amount of cracking occurred in the polyimide wire enamel coating. This may be because the thermal expansion coefficients of polyimide and carbon fiber may be different. When the material undergoes temperature changes, the difference in thermal expansion coefficients may cause internal stress, thereby causing the paint film to crack, thereby affecting the improvement effect of carbon fiber powder on the mechanical properties of polyimide wire enamel. The present invention further introduces the above technical problem and performs modification on carbon fiber powder. On the one hand, the surface of carbon fiber is corroded by acid oxidation, so that the surface of carbon fiber is loaded with more active oxygen-containing functional groups and the surface is roughened, and the binding force between polyimide resin and carbon fiber is increased by physical action. On the other hand, polyamide-amine is grafted on the surface of the fiber, so that the surface of carbon fiber is loaded with more amino groups, which have hydrogen bonding force with amino groups on polyimide molecules. The present invention improves the binding force between carbon fiber powder and polyimide resin paint through the above two effects, thereby avoiding subsequent paint film cracking due to temperature changes, and further improving the mechanical properties of wire enamel.

[0017] Preferably, the acid oxidation treatment time in step 11) is 20-60 min.

[0018] Preferably, the heating reaction temperature in step 12) is 50-60° C., and the heating reaction time is 1-3 h.

[0019] Preferably, in step 13), the mass ratio of the pre-modified carbon fiber to the polyamide-amine is 1:0.2-0.8;

[0020] The stirring reaction time is 3h.

[0021] In the technical solution of the present invention, in order to form a stable binding force between the carbon fiber powder and the polyimide resin, the surface of the carbon fiber powder must be loaded with a sufficient amount of amino groups. Through experiments, it is found that the mass ratio of modified carbon fiber to polyamide-amine is less than 1:0.2, and a stable force can be formed between the carbon fiber powder and the polyimide resin. However, when the mass ratio of modified carbon fiber to polyamide-amine is less than 1:0.8, the team of the present invention unexpectedly found that with the increase of the amount of polyamide-amine, the thermal stability of the wire enamel decreased, which was unexpected by the team of the present invention. This may be because the molecular structure of polyamide-amine contains more aliphatic or flexible segments, which are prone to thermal motion at high temperatures, resulting in weakened interactions between molecular chains, thereby reducing the overall thermal stability.

[0022] A high-strength enameled copper flat wire is prepared by the method.

[0023] The present invention has the following beneficial effects:

[0024] 1) Improve the mechanical strength of polyimide wire enamel by adding carbon fiber powder to it. Carbon fiber has the characteristics of high modulus and high strength, can evenly distribute stress and reduce stress concentration. When carbon fiber is evenly dispersed in the polyimide matrix, it can effectively bear the load, thereby improving the mechanical properties of the material;

[0025] 2) The carbon fiber powder is modified. On the one hand, the surface of the carbon fiber is corroded by acid oxidation, so that the surface of the carbon fiber is loaded with more active oxygen-containing functional groups and the surface is roughened, and the binding force between the polyimide resin and the carbon fiber is increased by physical action. On the other hand, polyamide-amine is grafted on the fiber surface, so that the surface of the carbon fiber is loaded with more amino groups, which have hydrogen bonding force with the amino groups on the polyimide molecules. The present invention improves the binding force between the carbon fiber powder and the polyimide resin paint through the above two effects, thereby avoiding the subsequent paint film cracking due to temperature changes, and further improving the mechanical properties of the wire enamel. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] A method for preparing a high-strength enameled copper flat wire comprises the following steps:

[0029] 1) cresol and anhydrous ethanol are mixed in a volume ratio of 3:1 to obtain a mixed solvent, a polyimide resin with a solid content of 25% is added to the mixed solvent in a mass ratio of 1:80 to dissolve to obtain a polyimide solution, and modified carbon fiber powder is added to the polyimide solution, wherein the mass ratio of the modified carbon fiber powder to the polyimide is 1:15, and the mixture is stirred evenly to obtain a wire enamel;

[0030] 2) The wire enamel is evenly coated on the surface of the copper flat wire, the thickness of the wire enamel coated on the surface of the copper flat wire is controlled to be 40 um, and then heated and cured at 170° C. for 6 hours to obtain a high-strength enameled copper flat wire.

[0031] The preparation method of modified carbon fiber powder comprises the following steps:

[0032] 11) 50% nitric acid and acetone were mixed evenly in a volume ratio of 1:30, 2 g of carbon fiber powder was placed in a mixed solution of 100 mL of nitric acid and acetone for acid oxidation treatment for 50 min, and then filtered, separated, washed and dried to obtain oxidized carbon fiber powder;

[0033] 12) Add 1 g of γ-glycidyloxypropyltrimethoxysilane to a mixed solution of 70 mL of ethanol and 10 mL of water, stir and hydrolyze to obtain a hydrolyzate, add the above-obtained oxidized carbon fiber powder to the hydrolyzate, heat and react at 55° C. for 2 h, filter, separate, wash and dry to obtain a pre-modified carbon fiber powder;

[0034] 13) The pre-modified carbon fiber powder was added to a polyamide-amine aqueous solution with a mass concentration of 3%, the mass ratio of the pre-modified carbon fiber to the polyamide-amine being 1:07, heated to 80° C., stirred for reaction for 3 h, filtered, separated, washed and dried to obtain the modified carbon fiber powder.

[0035] Example 2

[0036] A method for preparing a high-strength enameled copper flat wire comprises the following steps:

[0037] 1) cresol and anhydrous ethanol are mixed in a volume ratio of 3:1 to obtain a mixed solvent, a polyimide resin with a solid content of 25% is added to the mixed solvent in a mass ratio of 1:80 to dissolve to obtain a polyimide solution, and modified carbon fiber powder is added to the polyimide solution, wherein the mass ratio of the modified carbon fiber powder to the polyimide is 1:15, and the mixture is stirred evenly to obtain a wire enamel;

[0038] 2) The wire enamel is evenly coated on the surface of the copper flat wire, the thickness of the wire enamel coated on the surface of the copper flat wire is controlled to be 40 um, and then heated and cured at 160° C. for 4 hours to obtain a high-strength enameled copper flat wire.

[0039] The preparation method of modified carbon fiber powder comprises the following steps:

[0040] 11) 50% nitric acid and acetone were mixed evenly in a volume ratio of 1:30, 2 g of carbon fiber powder was placed in a mixed solution of 100 mL of nitric acid and acetone for acid oxidation treatment for 30 min, and then filtered, separated, washed and dried to obtain oxidized carbon fiber powder;

[0041] 12) Add 1 g of γ-glycidyloxypropyltrimethoxysilane to a mixed solution of 70 mL of ethanol and 10 mL of water, stir and hydrolyze to obtain a hydrolyzate, add the above-obtained oxidized carbon fiber powder to the hydrolyzate, heat and react at 55° C. for 2 h, filter, separate, wash and dry to obtain a pre-modified carbon fiber powder;

[0042] 13) The pre-modified carbon fiber powder was added to a polyamide-amine aqueous solution with a mass concentration of 3%, the mass ratio of the pre-modified carbon fiber to the polyamide-amine being 1:0.3, heated to 80° C., stirred for reaction for 3 hours, filtered, separated, washed and dried to obtain the modified carbon fiber powder.

[0043] Example 3

[0044] A method for preparing a high-strength enameled copper flat wire comprises the following steps:

[0045] 1) cresol and anhydrous ethanol are mixed in a volume ratio of 3:1 to obtain a mixed solvent, a polyimide resin with a solid content of 25% is added to the mixed solvent in a mass ratio of 1:80 to dissolve to obtain a polyimide solution, and modified carbon fiber powder is added to the polyimide solution, wherein the mass ratio of the modified carbon fiber powder to the polyimide is 1:15, and the mixture is stirred evenly to obtain a wire enamel;

[0046] 2) The wire enamel is evenly coated on the surface of the copper flat wire, the thickness of the wire enamel coated on the surface of the copper flat wire is controlled to be 40 um, and then heated and cured at 165° C. for 5 hours to obtain a high-strength enameled copper flat wire.

[0047] The preparation method of modified carbon fiber powder comprises the following steps:

[0048] 11) 50% nitric acid and acetone were mixed evenly in a volume ratio of 1:30, 2 g of carbon fiber powder was placed in a mixed solution of 100 mL of nitric acid and acetone for acid oxidation treatment for 40 min, and then filtered, separated, washed and dried to obtain oxidized carbon fiber powder;

[0049] 12) Add 1 g of γ-glycidyloxypropyltrimethoxysilane to a mixed solution of 70 mL of ethanol and 10 mL of water, stir and hydrolyze to obtain a hydrolyzate, add the above-obtained oxidized carbon fiber powder to the hydrolyzate, heat and react at 55° C. for 2 h, filter, separate, wash and dry to obtain a pre-modified carbon fiber powder;

[0050] 13) The pre-modified carbon fiber powder was added to a polyamide-amine aqueous solution with a mass concentration of 3%, the mass ratio of the pre-modified carbon fiber to the polyamide-amine being 1:0.4, heated to 80° C., stirred for reaction for 3 hours, filtered, separated, washed and dried to obtain the modified carbon fiber powder.

[0051] Example 4

[0052] A method for preparing a high-strength enameled copper flat wire comprises the following steps:

[0053] 1) cresol and anhydrous ethanol are mixed in a volume ratio of 3:1 to obtain a mixed solvent, a polyimide resin with a solid content of 25% is added to the mixed solvent in a mass ratio of 1:80 to dissolve to obtain a polyimide solution, and modified carbon fiber powder is added to the polyimide solution, wherein the mass ratio of the modified carbon fiber powder to the polyimide is 1:15, and the mixture is stirred evenly to obtain a wire enamel;

[0054] 2) The wire enamel is evenly coated on the surface of the copper flat wire, the thickness of the wire enamel coated on the surface of the copper flat wire is controlled to be 50 um, and then heated and cured at 180° C. for 7 hours to obtain a high-strength enameled copper flat wire.

[0055] The preparation method of modified carbon fiber powder comprises the following steps:

[0056] 11) 50% nitric acid and acetone were mixed evenly in a volume ratio of 1:30, 2 g of carbon fiber powder was placed in a mixed solution of 100 mL of nitric acid and acetone for acid oxidation treatment for 60 min, and then filtered, separated, washed and dried to obtain oxidized carbon fiber powder;

[0057] 12) Add 1 g of γ-glycidyloxypropyltrimethoxysilane to a mixed solution of 70 mL of ethanol and 10 mL of water, stir and hydrolyze to obtain a hydrolyzate, add the above-obtained oxidized carbon fiber powder to the hydrolyzate, heat and react at 60° C. for 3 h, filter, separate, wash and dry to obtain a pre-modified carbon fiber powder;

[0058] 13) The pre-modified carbon fiber powder was added to a polyamide-amine aqueous solution with a mass concentration of 3%, the mass ratio of the pre-modified carbon fiber to the polyamide-amine being 1:0.8, heated to 80° C., stirred for reaction for 3 h, filtered, separated, washed and dried to obtain the modified carbon fiber powder.

[0059] Example 5

[0060] A method for preparing a high-strength enameled copper flat wire comprises the following steps:

[0061] 1) cresol and anhydrous ethanol are mixed in a volume ratio of 3:1 to obtain a mixed solvent, a polyimide resin with a solid content of 25% is added to the mixed solvent in a mass ratio of 1:80 to dissolve to obtain a polyimide solution, and modified carbon fiber powder is added to the polyimide solution, wherein the mass ratio of the modified carbon fiber powder to the polyimide is 1:15, and the mixture is stirred evenly to obtain a wire enamel;

[0062] 2) The wire enamel is evenly coated on the surface of the copper flat wire, the thickness of the wire enamel coated on the surface of the copper flat wire is controlled to be 30 um, and then heated and cured at 150° C. for 3 hours to obtain a high-strength enameled copper flat wire.

[0063] The preparation method of modified carbon fiber powder comprises the following steps:

[0064] 11) 50% nitric acid and acetone were mixed evenly in a volume ratio of 1:30, 2 g of carbon fiber powder was placed in a mixed solution of 100 mL of nitric acid and acetone for acid oxidation treatment for 20 min, and then filtered, separated, washed and dried to obtain oxidized carbon fiber powder;

[0065] 12) adding 1 g of γ-glycidyloxypropyltrimethoxysilane to a mixed solution of 70 mL of ethanol and 10 mL of water, stirring and hydrolyzing to obtain a hydrolyzate, adding the above-obtained oxidized carbon fiber powder to the hydrolyzate, heating and reacting at 50° C. for 1 h, filtering, separating, washing and drying to obtain a pre-modified carbon fiber powder;

[0066] 13) The pre-modified carbon fiber powder was added to a polyamide-amine aqueous solution with a mass concentration of 3%, the mass ratio of the pre-modified carbon fiber to the polyamide-amine being 1:0.2, heated to 80° C., stirred for reaction for 3 h, filtered, separated, washed and dried to obtain the modified carbon fiber powder.

[0067] Comparative Example 1

[0068] The difference between Comparative Example 1 and Example 1 is that:

[0069] No modified carbon fiber powder is added during the preparation of high-strength enameled copper flat wire.

[0070] The operation steps are the same as those in Example 1.

[0071] Comparative Example 2

[0072] The difference between Comparative Example 2 and Example 1 is:

[0073] In the preparation process of high-strength enameled copper flat wire, the modified carbon fiber powder is replaced with ordinary carbon fiber powder.

[0074] The operation steps are the same as those in Example 1.

[0075] Comparative Example 3

[0076] The difference between Comparative Example 3 and Example 1 is that:

[0077] Step 11) is omitted in the preparation process of the modified carbon fiber powder.

[0078] The operation steps are the same as those in Example 1.

[0079] Comparative Example 4

[0080] The difference between Comparative Example 4 and Example 1 is that:

[0081] In the preparation process of the modified carbon fiber powder, steps 12) and 13) are omitted, and the operation steps are the same as those in Example 1.

[0082] Comparative Example 5

[0083] The difference between Comparative Example 5 and Example 5 is:

[0084] During the preparation of modified carbon fiber powder,

[0085] The mass ratio of the pre-modified carbon fiber to the polyamide-amine is 1:0.1, and the operation steps are the same as those in Example 5.

[0086] Comparative Example 6

[0087] The difference between Comparative Example 6 and Example 4 is that:

[0088] During the preparation of modified carbon fiber powder,

[0089] The mass ratio of the pre-modified carbon fiber to the polyamide-amine is 1:0.9, and the operation steps are the same as those in Example 4.

[0090] Comparative Example 7

[0091] The difference between Comparative Example 7 and Example 4 is that:

[0092] During the preparation of modified carbon fiber powder,

[0093] The mass ratio of the pre-modified carbon fiber to the polyamide-amine is 1:1, and the operation steps are the same as those in Example 4.

[0094] Comparative Example 8

[0095] The difference between Comparative Example 8 and Example 4 is that:

[0096] During the preparation of modified carbon fiber powder,

[0097] The mass ratio of pre-modified carbon fiber to polyamide-amine is 1:1.1.

[0098] The operation steps are the same as those in Example 4.

[0099] Performance Testing

[0100] 1. Mechanical properties test:

[0101] The mechanical properties of polyimide paint film at room temperature were measured using the CMT-4254 electronic universal testing machine produced by Shenzhen SUNS. The paint film specimens were prepared according to GB / T1040 standard, with a specimen size of 10×1.25cm, a tensile speed of 20mm.min-1, and an original gauge length of 2cm. Five specimens were tested in parallel for each group of specimens, and the average value was calculated.

[0102] 2. Thermal stability test

[0103] The thermal stability of the polyimide film was determined using a DTG-60 thermogravimetric analyzer produced by Shimadzu Corporation of Japan. The ambient atmosphere was nitrogen, the nitrogen flow rate was 20 ml / min, the heating rate was 10 °C / min, the sample mass was 5 mg, the sample heating range was 30-800 °C, and the temperature T was recorded when the polyimide film lost 5% of its weight. 5% , when the temperature is raised to 800℃, the residual rate of the sample is recorded.

[0104]

[0105]

[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-strength enameled copper flat wire, characterized in that: The following steps are involved: Adding polyimide resin into a solvent to dissolve to obtain a polyimide solution, adding modified carbon fiber powder into the polyimide solution, stirring evenly, and obtaining wire enamel; The enameled wire varnish is evenly coated on the surface of the copper flat wire, and then heated and cured to obtain a high-strength enameled copper flat wire.

2. The method for preparing a high-strength enameled rectangular copper wire according to claim 1, characterized in that: In the step 2), the thickness of the wire enamel coated on the surface of the copper flat wire is controlled to be 30-50 um.

3. The method for preparing a high-strength enameled rectangular copper wire according to claim 1, characterized in that: In the step 2), the heating curing temperature is 150-180° C., and the heating curing time is 3-7 hours.

4. The method for preparing a high-strength enameled rectangular copper wire according to claim 1, characterized in that: The method for preparing the modified carbon fiber powder in step 1) comprises the following steps: 11) placing the carbon fiber powder in a mixed solution of nitric acid and acetone for acid oxidation treatment, filtering, separating, washing and drying to obtain oxidized carbon fiber powder; 12) adding γ-glycidyloxypropyltrimethoxysilane to a mixed solution of ethanol and water, stirring and hydrolyzing to obtain a hydrolyzate, adding the oxidized carbon fiber powder to the hydrolyzate, heating for reaction, filtering, separating, washing and drying to obtain a pre-modified carbon fiber powder; 13) Add the pre-modified carbon fiber powder into the polyamide-amine aqueous solution, heat to 80° C., stir to react, filter, separate, wash and dry to obtain the modified carbon fiber powder.

5. The method for preparing a high-strength enameled rectangular copper wire according to claim 4, characterized in that: The acid oxidation treatment time in step 11) is 20-60 minutes.

6. The method for preparing a high-strength enameled rectangular copper wire according to claim 4, characterized in that: In the step 12), the heating reaction temperature is 50-60° C., and the heating reaction time is 1-3 hours.

7. The method for preparing a high-strength enameled rectangular copper wire according to claim 4, characterized in that: In the step 13), the mass ratio of the pre-modified carbon fiber to the polyamide-amine is 1:0.2-0.8; The stirring reaction time is 3h.

8. A high-strength enameled copper flat wire, characterized in that: The method is prepared by any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of carbon fiber reinforcement grafted by graphene oxide

    CN102409528A

  • Microwave ultrasonic co-processing type chemical surface modification method and microwave ultrasonic co-processing type chemical surface modification device for carbon fiber

    CN104032565A

  • Heat-resistant anti-rust wax

    CN108949025A

  • Carbon fiber grid, preparation method thereof, composite material and preparation of composite material

    CN110144733A

  • Modified carbon fiber based on macromolecular amine concave-convex structure and preparation method of modified carbon fiber

    CN113430832A